Contexto tectônico dos granitóides neoproterozóicos da faixa de dobramentos paraguai, MS e MT - Manzano, Jefferson Cassu [UNESP] (2008)
The Neoproterozoic Granitic Province from the southeast of Mato Grosso and Mato Grosso do Sul region is constituted by seven distinctive granitic bodies, emplaced in the epimetamorphic rocks of the Cuiabá Group and related to the evolution of Paraguai Folded Belt. The Northern portion crops out in Mato Grosso State and is constituted by São Vicente, Araguaiana and Lajinha batholiths; the Southern portion crops out in the Mato Grosso do Sul State and is represented the Sonora, Coxim Rio Negro and Taboco massifs. The structural evolution is evidenced by the presence of three deformational phases, the first one is characterized by axial planar foliation (S 1), parallel or sub parallel to S 0, with attitude N60E/70NW; the second constitutes the most important phase for the tectonic arrangement and is defined by a slaty and/or crenulation cleavages (S 2), with attitude N10W/30SW and contact metamorphism associated to the emplacement of granitic bodies, the third phase is characterized by a weak retrometamorphic cleavage (S 3) with attitude N10E/ 80NW, that evolves local and gradually to strike-slip shear zones. The geological data suggest that this province was formed syn- to post tectonic to the D2 deformational set associated to the end of the collisional event in the Southeastern of the Amazonian Craton.